An Empirical Parameterization to Separate Coarse and Fine Mode Aerosol Optical Depth Over Land - Xiaohan Li; Paul Ginoux (Geophysical Research Letters)
Abstract Retrieving the fine‐mode fraction (FMF) of aerosol optical depth from satellite data is crucial for understanding the impact of natural versus anthropogenic aerosols on climate and air quality. However, few high‐quality global FMF products from MODIS exist. To address this gap, this study derives a new formulation of FMF as a function of the Ångström exponent (AE) based on over 20 years of AERONET measurements. Our results reveal a consistent FMF‐AE relationship across continental regions, supporting the feasibility of globally estimating FMF through a simple empirical function based on AE. Validation with independent NOAA GML data sets shows predicted FMF errors mostly within 0.1. Finally, applying this parameterization to MODIS Aqua and Terra data significantly improved satellite‐derived FMF agreement with AERONET compared to previous derivations. This parameterization provides a simple, valuable tool for accurately deriving FMF over land from MODIS and understanding its impact on climate and air quality.